1977
DOI: 10.1111/j.1365-2265.1977.tb01989.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Fluctuations in Plasma Cortisol in Cushing's Syndrome

Abstract: Short-term fluctuations in plasma cortisol were determined overnight in twelve patients with Cushing's syndrome: eight patients with bilateral adrenal hyperplasia of hypothalamic-pituitary orgin, three patients with a cortisol producing adenoma and one patient with a carcinoma of the adrenal cortex. While either secretory episodes in plasma cortisol or a fixed pattern of cortisol secretion were observed both in patients with pituitary dependent and in those with pituitary independent hypercorticism, a typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…The findings in respect of the other patients are also in agreement with our report save in one adenoma case, where there ap¬ pears to be a diurnal variation in the plasma cortisol concentration. Other investigators have also reported results in some cases differing from our findings (Vetter et al 1977;Olsen et al 1978). The reason for these discordant results warrants further investigation.…”
Section: Discussioncontrasting
confidence: 80%
“…The findings in respect of the other patients are also in agreement with our report save in one adenoma case, where there ap¬ pears to be a diurnal variation in the plasma cortisol concentration. Other investigators have also reported results in some cases differing from our findings (Vetter et al 1977;Olsen et al 1978). The reason for these discordant results warrants further investigation.…”
Section: Discussioncontrasting
confidence: 80%
“…The available literature is not clear on this. But this could very well be a reflection of fluctuation in cortisol secretion in patients with Cushing’s syndrome, rather than real suppression 16 18. Because microadenomas can be detected in up to 10–20% of individuals without known pituitary disease,19 a positive imaging study does not prove Cushing’s disease as we also learnt from this patient.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors suggested that the secretory pattern may help the differential diagnosis of the various aetiologies of the syndrome Tourniaire et al 1971;Vagnucci 1979;Yoshida et al 1979). Others (Sederberg-Olsen et al 1973;Vetter et al 1977;Olsen 1978) claimed that this parameter could not discriminate between pa¬ tients with pituitary-dependent or pituitaryindependent Cushing's syndrome. However, with only one exception (Vagnucci 1979), these con¬ trasting conclusions were solely based on the visual examination of the data.…”
mentioning
confidence: 97%